Pengaruh Bauran Pemasaran Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada PT Indomarco Pratama Denpasar Bali - Gde Indra Surya Diputra; Gede Agus Dian Maha Yoga (Widya Manajemen, 2020)
This study discusses analyzing the marketing mix and service quality of purchasing decisions at PT. Indomarco Pratama Denpasar Bali. This research method is quantitative descriptive using questionnaires as a method of data collection and multiple linear regression analysis using SPSS. The results showed that the promotional mix involved a partial purchase decision of consumers at PT Indomarco Pratama Denpasar Bali by 0.002 <0.05, with a dominant product, price, and promotion indicators, starting to look for indicators of other places, people, physical evidence, processes. PT. Indomarco Pratama Denpasar Bali is 0.003 <0.05, with dominant Empathy, Reliability, Responsiveness indicators, then tangibles indicators, guarantees accepted. Simultaneously the marketing mix and service quality influence the purchasing decision of 0,000 <0.05. These results also answer the three hypotheses of this study. The results show that the marketing mix and the quality of services offered are positive and significant for purchasing decisions. The results have the meaning of increasing marketing mix and service quality, so the purchasing decisions at PT Indomarco Pratama Denpasar Bali will also increase.